Analisis Pelaksanaan Pencatatan Dan Evaluasi Petty Cash Pada PT. Cahaya Benteng Mas Makassar - Anggreni, Indri; Pasanda, Erna; Yessica, Maria (Universitas Multi Data Palembang, 2025)
Petty cash is a fund used by companies to finance operational activities that are relatively small and routine. In this study to understand the implementation of recording petty cash funds at PT Cahaya Benteng Mas Makassar, information acquisition is carried out through observation, interviews, and archives with a qualitative descriptive approach. Research findings show that the implementation of recording petty cash funds at PT Cahaya Benteng Mas Makassar is carried out by determining the total money that is always constant (imprest method) in each period, adding or refilling petty cash funds is done at the end of the period or when the amount of petty cash funds has decreased. In its operations, there are procedures for implementation and various records that are applied, such as the establishment of petty cash funds and top-ups of petty cash funds when all procedures have been carried out and approved by the head of finance, although there are still some weaknesses in its internal control caused by the lack of order in the implementation of recording petty cash funds.